2001
DOI: 10.1111/1467-9817.00133
|View full text |Cite
|
Sign up to set email alerts
|

Helping parents to read with their children: evaluation of an individual and group reading motivation programme

Abstract: Twenty-two primary school children, aged 6±12 years, who were experiencing significant reading difficulties, were allocated to one of two parent-instruction treatment conditions according to the parent's preference. The treatments were based upon learning-theory principles, and were aimed at teaching the parents optimal ways of helping their child learn to read. One condition involved the parent and child being seen individually by the therapist twice a week over five weeks. The other condition involved the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…Large increases in home reading attitude were reported for students receiving parent tutoring from parents participating in individual training in comparison to parents trained as a group (ES ¼ 1.71: Collins & Matthey, 2001). One study also reported one treatment group (typical basal instruction with researcher support) had improved attitudes towards reading; however, there were no significant differences in attitude reported for any other treatment groups in this study (Foorman, 1998).…”
Section: Attitude Measurescontrasting
confidence: 52%
See 1 more Smart Citation
“…Large increases in home reading attitude were reported for students receiving parent tutoring from parents participating in individual training in comparison to parents trained as a group (ES ¼ 1.71: Collins & Matthey, 2001). One study also reported one treatment group (typical basal instruction with researcher support) had improved attitudes towards reading; however, there were no significant differences in attitude reported for any other treatment groups in this study (Foorman, 1998).…”
Section: Attitude Measurescontrasting
confidence: 52%
“…This includes Reading Recovery, reading skill instruction (e.g., word reading, phonics), guided oral reading, and=or strategy instruction. Seven studies examined the effects of one-on-one reading instruction for students with reading problems: five of these studies reported overall positive effects on social outcomes (Abikoff et al, 1988;Buck, Warr-Leeper, & Evans, 1988;Coie & Krehbiel, 1984;Collins & Matthey, 2001;Traynelis-Yurek & Hansell, 1993), while two studies found negative effects on self-concept (Chapman et al, 2001;Rumbaugh & Brown, 2000). Jenkins et al (1994) described an intervention that incorporated three of the previous interventions: group interactive learning for all students, cross-age tutoring=peer tutoring, and small group reading instruction as needed.…”
Section: One-on-one Remedial Readingmentioning
confidence: 99%
“…Reading groups (also known as book clubs) are groups of people who read the same books and dedicate time to discuss them jointly and informally (Collins, 2022). Some books traditionally end with suggestions of potential questions to be debated.…”
Section: The Role Of Reading Programmesmentioning
confidence: 99%
“…As such, effective literacy tutoring -be it in whole-class, small group or one-onone situations -encompasses an array of diverse and sophisticated skills and understandings. Following studies by Neuman (1995), Roe and Vukelich (2001) and Collins and Matthey (2001), for instance, Woolley and Hay observe, "tutors require explicit information on how to implement instructional strategies when tutoring children" (2007, p. 13). Further, "the tasks assigned to tutors must be consistent with what they can easily and willingly accomplish" (2007, p. 13), which further highlights the importance of selfmonitoring and other interpersonal skills.…”
Section: Indigenous Assistant Teachers and Educational Reform: Theorymentioning
confidence: 99%